2013
DOI: 10.1177/1533317513488922
|View full text |Cite
|
Sign up to set email alerts
|

Incentives and Barriers to Research Participation and Brain Donation Among African Americans

Abstract: Successful African American recruitment for aging research requires sensitivity to factors that influence participation. In this work, a structured face to face educational interview was used to recruit African Americans for a longitudinal aging study and to collect information about attitudes related to research. The interview was designed to build trust and respect for research and to educate participants about the need for minority participants. Of the 91 African Americans aged 65 and older who completed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
39
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 16 publications
0
39
1
Order By: Relevance
“…This moderating effect may be related to our findings in prior qualitative research in which we found that Chinese research volunteers and their family members often expressed the desire for the body to remain whole after one dies and the high value the Chinese participants placed on family decision-making around brain donation. 14 In contrast to our findings with respect to Asian ethnicity, we found that Hispanic ethnicity was only associated with willingness to be a brain donor in the final model and this association was positive. Further research is needed to more fully explicate the factors that influence the receptivity of these and other ethnic groups to brain donation.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This moderating effect may be related to our findings in prior qualitative research in which we found that Chinese research volunteers and their family members often expressed the desire for the body to remain whole after one dies and the high value the Chinese participants placed on family decision-making around brain donation. 14 In contrast to our findings with respect to Asian ethnicity, we found that Hispanic ethnicity was only associated with willingness to be a brain donor in the final model and this association was positive. Further research is needed to more fully explicate the factors that influence the receptivity of these and other ethnic groups to brain donation.…”
Section: Discussioncontrasting
confidence: 99%
“…An alternative interpretation is that older respondents may have had the opportunity for greater reflection about the ending of their lives, may be more comfortable considering the ultimate disposition of their bodies, and/or may be more decisive about and open to brain donation. The first interpretation (along with the correlation of age and length of duration as a study volunteer) is supported by Schnieders et al 14 who found that longer term enrollment as a study volunteers was associated with greater likelihood of agreeing to brain donation. The reason behind the significance of Latino ethnicity as a predictor of willingness to donate one’s brain is unclear, especially since this relationship was not significant in the baseline model or the subsequent domain-specific models.…”
Section: Discussionmentioning
confidence: 88%
“…In general, African Americans are much less likely to agree to brain donation [70], which contributed to the difficulty in obtaining these samples. However, efforts are underway to increase such donations [71,72]. Only one of the brain banks that contributed tissue to this study collected information on current medications; thus, it is not clear if ethnicity-related differences in medication use may have impacted the results.…”
Section: Discussionmentioning
confidence: 97%
“…Many articles have published goals and strategies for recruiting Blacks/African Americans and other marginalized groups into clinical studies—one major goal discussed in these articles is to build long-term trust within the Black/African American community [35, 40, 84]. Some recommendations for building trust are as follows: 1) publicly acknowledging the historical mistreatment of Blacks/African Americans in biomedical research [24, 36, 8385], 2) adequately explaining the consent process [24, 36, 86], and protections in place to prevent mistreatment, 3) engaging in ongoing Q&A discussions with the community [24, 30, 40, 84, 85, 87, 88], and 4) creating relationships that include patients, caregivers, health-care providers, community leaders, researchers, and study coordinators [89]. Secondly, ADCs should actively enroll Blacks/African Americans, attach specific research questions, and perform power analyses so that it can be ensured that comparisons among individuals from different racial/ethnic groups will be valid.…”
Section: Addressing the Problem: Considerations For The Fieldmentioning
confidence: 99%
“…It is important to have a culturally diverse group of experts included in the research team [36, 84, 87]. One long-term strategy for ADCs can be to increase African American representation among clinicians, scientists, epidemiologists, biostatisticians, and study coordinators to aid in experimental design and data analysis of AD and related dementias within the Black/African American population.…”
Section: Addressing the Problem: Considerations For The Fieldmentioning
confidence: 99%